THE EFFECT OF ADVERSITY QUOTIENT AND ATTITUDES OF STUDENTS ON THE STUDENT'S PHYSICAL LEARNING ACHIEVEMENTS - Nor Hanifah; Abdul Salam M; Dewi Dewantara (JURNAL PENA SAINS, 2021)
This ex post facto study aimed to reveal the influence of adversity quotient and attitudes students on physics learning achievement.  The population of this study was all of twelvh graders of Public Senior High School (SMAN) 10 Banjarmasin City. The sample was determined by simple random sampling. The instruments used were questionnaires. The research data were analyzed by using SPSS statistical data processing program. The results showed that adversity quotient and attitudes students were in the very high and positive category, and than had a significant effect on physics learning achievement of Public Senior High School (SMAN) 10 Banjarmasin City.